The Implementation of Genre-based Approach in Teaching English at The second Year of Universitas Muhammadiyah Kalimantan Timur. - Sunarti Sunarti; Rani Herning Puspita; Dzul Rachman (Acitya: Journal of Teaching and Education, 2019)
The objectives of the study were: (1) Describe the procedures used by the teacher in teaching English based on Genre-based Approach; (2) Describe the types of the classroom activities using Genre-based Approach; (3) Describe the problems faced by the teacher and the solution in teaching English using Genre-based Approach. The population of the research is the second year students of English department of UMKT in the academic year of 2018/2019. The samples were from one class. In taking the sample, total sampling approach was used. The data in this research were information about the teaching strategies and difficulties faced by the teacher on teaching English based on GBA and also the difficulties faced by the students of second year at UMKT. In collecting the data, it was taken from the sources by employing observation interview, and document. There were three main components of analyzed data, namely: (1)Reduction of Data; (2) Display the Data; (3) Interpreting. The research finding of this study were: (1) The Procedure of Teaching English: By GBA, the teacher feels easier to deliver the material; (2) Classroom Activities: Based on the implementation of School-based Curriculum in teaching English, the teacher conducted several classroom activities that consist of four cycles, namely BKOF, MOT, JCOT, and ICOT; (3) Problem faced by Teacher: The problems are the student's difficulty in vocabulary and pronunciation, teacher’s difficulty in manage the time. To solve this problem the teacher should give more attention to the students that less in capability rather than general students.